(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
As you know, the term “translation” has many meanings. On the one hand, it denotes an activity that consists in transmitting the content of information in one language by means of another language, however, on the other hand, translation represents the very results of this activity. Throughout the world, translation has become a universal activity. Bilingualism as a concept is founded within the framework of psycholinguistics by various scientists who have divergent ideas about its role in translation theory. What is translation activity? What is bilingualism? What are the specific functions of bilingualism in the general theory of translation? In this article we will try to answer the questions posed.